Quality of life in children with skin disease: A Spanish sample - Lucía Campos-Muñoz; Cristina Belmar Madrid; Alberto Conde-Taboada; Alvaro Iglesias Puzas; Elena Gonzalez Guerra; Eduardo López-Bran (Elsevier, 2023)
Introduction: The impact of skin diseases on quality of life varies widely, and some can have an impact similar to that of asthma or cystic fibrosis. Material and methods: We conducted a cross-sectional, observational and descriptive study with the aim of describing the degree to which quality of life was affected in paediatric patients managed in a dermatology clinic by means of the Children's Dermatology Life Quality Index (CDLQI). Results: In our study, the skin disease with the greatest impact on quality of life was atopic dermatitis, chiefly on account of symptoms like pruritus and insomnia. It was followed by acne, mainly due to the associated negative feelings (shame, sadness, etc.). Quality of life in patients with viral warts and molluscum contagiosum was mostly affected by the treatment, chiefly based on cryotherapy. Most patients with nevi or café-au-lait spots did not have a decreased quality of life, although up to one third of them had negative feelings in relation to their skin disease. Discussion: Atopic dermatitis was the common skin disease that caused the greatest impairment in quality of life in our sample, although other diseases also had an impact on different dimensions of quality of life. We ought to underscore the recommendation to use less painful treatments than cryotherapy for viral warts and molluscum contagiosum, as the impairment in quality of life in paediatric patients with these conditions was mainly due to the treatment. Resumen: Introducción: Las enfermedades cutáneas pueden afectar a la calidad de vida de forma muy variable; el impacto de algunas dermatosis puede ser similar al del asma o la fibrosis quística. Material y métodos: Realizamos un estudio observacional, descriptivo y transversal con el objetivo de describir el grado de afectación de la calidad de vida de los niños que acudieron a la consulta monográfica de Dermatología Pediátrica, mediante el Children's Dermatology Life Quality Index (CDLQI). Resultados: En este estudio la dermatosis con mayor impacto en la calidad de vida fue la dermatitis atópica, debido principalmente a síntomas como el prurito y el insomnio. El segundo grupo diagnóstico con mayor afectación fue el acné, debido principalmente a los sentimientos negativos (vergüenza, tristeza, etc.) asociados al mismo. Los pacientes con verrugas víricas y moluscos contagiosos tuvieron impacto en la calidad de vida debido principalmente al tratamiento de los mismos, que se realizó principalmente con crioterapia. La mayor parte de los pacientes con nevus o manchas café con leche no tuvieron afectación en la calidad de vida, si bien hasta un tercio de ellos tuvieron sentimientos negativos secundarios a su dermatosis. Discusión: La dermatitis atópica fue la enfermedad dermatológica común que más impactó en la calidad de vida en nuestra muestra de pacientes, aunque otros procesos también afectaron a la calidad de vida en distintos aspectos de la misma. Cabe destacar la recomendación de emplear en verrugas víricas y moluscos contagiosos tratamientos más indoloros que la crioterapia, ya que es el tratamiento lo que más impacta en la calidad de vida de los pacientes pediátricos.